Question about Office Equipment & Supplies

With the insertion of a plus sign it's "a squared plus b squared is equal to c squared." Applied to the Pythagorean Theorem it's "the sum of the squares of the sides is equal to the square of the hypotenuse."

Posted on Jul 12, 2013

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

Assuming the first '2' means "squared" then the equation is already correct for certain values of 'x'.

Apr 05, 2013 | Mathsoft Computers & Internet

pemdas, parentheses,exponent,multiply,divide,add,subtract. best I can do been out of school for awhile! Hope it helps.

Apr 05, 2013 | Mathsoft Computers & Internet

Apply what you learned, especially that this system is quite simple.

Elimination

1. entails eliminating one variable to find (in this case) a single equation involving the other variable.

2. Solve that new equation, meaning isolate the variable that was not eliminated.

3. Substitute the value found in the last step and replace it in one of the original equation to obtain the other variable.

x+y=10

x-y=-6

Add the left sides to get x+y+x-y=2x

Add the right sides of the system to obtain 10+(-6)=4

Write Sum of left sides =Sum of right sides or 2x=4.

Since this new equation involves only x, you can solve it for x, getting x=4/2=2

Now you know the value of x (=2)

Take one of the original equations (for example x+y=10) and put 2 in place of x.

The equation becomes 2+y=10

Solve it to obtain y=10-2=8

Thus your solution is x=2, y=8

Check: use one equation in which you substitute 2 for x and 8 for y: x-y=-6 becomes 2-8=-6

Verified.

In the general case you will have to multiply by certain values to obtain opposite coefficients for the same variable. Here that was not necessary because the coefficient of y is 1 in the first equation and -1 in the second.

Elimination

1. entails eliminating one variable to find (in this case) a single equation involving the other variable.

2. Solve that new equation, meaning isolate the variable that was not eliminated.

3. Substitute the value found in the last step and replace it in one of the original equation to obtain the other variable.

x+y=10

x-y=-6

Add the left sides to get x+y+x-y=2x

Add the right sides of the system to obtain 10+(-6)=4

Write Sum of left sides =Sum of right sides or 2x=4.

Since this new equation involves only x, you can solve it for x, getting x=4/2=2

Now you know the value of x (=2)

Take one of the original equations (for example x+y=10) and put 2 in place of x.

The equation becomes 2+y=10

Solve it to obtain y=10-2=8

Thus your solution is x=2, y=8

Check: use one equation in which you substitute 2 for x and 8 for y: x-y=-6 becomes 2-8=-6

Verified.

In the general case you will have to multiply by certain values to obtain opposite coefficients for the same variable. Here that was not necessary because the coefficient of y is 1 in the first equation and -1 in the second.

Aug 16, 2011 | Casio Office Equipment & Supplies

Definition

A mathematical statement used to evaluate a value. An equation can use any combination of mathematical operations, including addition, subtraction, division, or multiplication. An equation can be already established due to the properties of numbers (2 + 2 = 4), or can be filled solely with variables which can be replaced with numerical values to get a resulting value. For example, the equation to calculate return on sales is: Net income ÷ Sales revenue = Return on Sales. When the values for net income and sales revenue are plugged into the equation, you are able to calculate the value of return on sales.

There are many types of mathematical equations.

1. Linear Equations y= mx + b (standard form of linear equation)

2. Quadratic Equations y= ax^2+bx+c

3. Exponential Equations y= ab^x

4. Cubic Equations y=ax^3+ bx^2+cx+d

5. Quartic Equations y= ax^4+ bx^3+ cx^2+ dx+ e

6. Equation of a circle (x-h)^2+(y-k)^2= r^2

7. Constant equation y= 9 (basically y has to equal a number for it to be a constant equation).

8. Proportional equations y=kx; y= k/x, etc.

Jun 14, 2011 | Computers & Internet

We find volume by using V = H*W*L , where H = height , W = width, and L = length. You say H = 2 ft,

V = 80 ft ^3, and W = L - 3 . Put all of these back onto the equation and we will have

80 = 2 * (L - 3) * L . We can condense this to be 80 = (2*L - 2*3 ) * L then becomes 80 = 2*L*L - 2*3*L

simplifying this we get 40 = L*L - 3*L . This is also 40 = L * (L - 3) this is a quadratic equation, meaning that

we will get two answers for L. In this case L = 0 and L = 3. Since 0 ft would mean that the tool box doesn't

have a length we will use L = 3. We can now put this back into our original equation to find out what the

width is. 80 = 2 * W * 3, this is 80/6 = W = 13.3333 . Now we know that W = 13.3333 and L = 3.

V = 80 ft ^3, and W = L - 3 . Put all of these back onto the equation and we will have

80 = 2 * (L - 3) * L . We can condense this to be 80 = (2*L - 2*3 ) * L then becomes 80 = 2*L*L - 2*3*L

simplifying this we get 40 = L*L - 3*L . This is also 40 = L * (L - 3) this is a quadratic equation, meaning that

we will get two answers for L. In this case L = 0 and L = 3. Since 0 ft would mean that the tool box doesn't

have a length we will use L = 3. We can now put this back into our original equation to find out what the

width is. 80 = 2 * W * 3, this is 80/6 = W = 13.3333 . Now we know that W = 13.3333 and L = 3.

Mar 07, 2011 | Office Equipment & Supplies

Ah, word problems! The trick is to convert the given information into two equations in two unknowns. Let's let S be the number of solid color rolls sold, and P be the number of print rolls.

The first equation is easy:

(eq. 1): S + P = 480

We're given that information: the total number of rolls sold. For the second equation, use the given price information ($4/roll for the plain, $6/roll for the print).

(eq. 2): 4S + 6P = 2340

Again, we're given the total sales, and we know how much each kind costs.

Now it's just some basic algebra. Let's rearrange equation 1 to get S by itself:

S = 480 - P

Then use that value in equation 2, and solve for P:

4S + 6P =2340

4(480 - P) + 6P = 2340

1920 - 4P + 6P = 2340

2P = 420

P = 210

Now we know that the MLHS band sold 210 rolls of print paper, which means they sold 270 rolls of solid. You can your answers in the original equations. If they are the right values, both equations will work out.

270 + 210 = 480, eq. 1 is right.

(4 x 270) + (6 X 210) = 1080 + 1260 = 2340, eq. 2 checks.

The first equation is easy:

(eq. 1): S + P = 480

We're given that information: the total number of rolls sold. For the second equation, use the given price information ($4/roll for the plain, $6/roll for the print).

(eq. 2): 4S + 6P = 2340

Again, we're given the total sales, and we know how much each kind costs.

Now it's just some basic algebra. Let's rearrange equation 1 to get S by itself:

S = 480 - P

Then use that value in equation 2, and solve for P:

4S + 6P =2340

4(480 - P) + 6P = 2340

1920 - 4P + 6P = 2340

2P = 420

P = 210

Now we know that the MLHS band sold 210 rolls of print paper, which means they sold 270 rolls of solid. You can your answers in the original equations. If they are the right values, both equations will work out.

270 + 210 = 480, eq. 1 is right.

(4 x 270) + (6 X 210) = 1080 + 1260 = 2340, eq. 2 checks.

Dec 13, 2010 | Computers & Internet

The best way to solve this is to develop one or more equations and then solve for the unknown numbers.

I solved this problem twice using different sets of equations to make sure I was right, and here is what I found:

1) I used the equations x + y = 623, and x = (2/3)y. In these equations, x is the number of girls and y is the number of boys.

Substituting the second equation into the first, I get (2/3)y + y = 623.

Adding the left side together I get : (5/3)y = 623.

Dividing both sides by (5/3) I get 373.8.

This means that x (the number of girls) is 249.2.

2) For the second attempt, I developed the equation: 2x+3x=623. Here 2x is the number of girls, and 3x is the number of boys.

Adding the left side I get: 5x = 623.

Dividing both sides by 5 I get: x = 124.6.

This means that the number of girls (2x) is 249.2. Just like in the first method.

But since you can't have a 1/5 of a girl, the answer must be 249 girls.

I solved this problem twice using different sets of equations to make sure I was right, and here is what I found:

1) I used the equations x + y = 623, and x = (2/3)y. In these equations, x is the number of girls and y is the number of boys.

Substituting the second equation into the first, I get (2/3)y + y = 623.

Adding the left side together I get : (5/3)y = 623.

Dividing both sides by (5/3) I get 373.8.

This means that x (the number of girls) is 249.2.

2) For the second attempt, I developed the equation: 2x+3x=623. Here 2x is the number of girls, and 3x is the number of boys.

Adding the left side I get: 5x = 623.

Dividing both sides by 5 I get: x = 124.6.

This means that the number of girls (2x) is 249.2. Just like in the first method.

But since you can't have a 1/5 of a girl, the answer must be 249 girls.

Nov 19, 2009 | Office Equipment & Supplies

Hi romanam

If spoon is "s" and fork is "f"

you get 2 equations like:

4s + 3f = 15 equation 1

4s + 1f = 13 equation 2

Equation (1) - equation (2) gives :

2f = 2 which means

1f = 1 (dividing both sides by 2)

! fork costs $1

5 forks cost $5

If you are happy with the answer, please give a rating

luciana44

If spoon is "s" and fork is "f"

you get 2 equations like:

4s + 3f = 15 equation 1

4s + 1f = 13 equation 2

Equation (1) - equation (2) gives :

2f = 2 which means

1f = 1 (dividing both sides by 2)

! fork costs $1

5 forks cost $5

If you are happy with the answer, please give a rating

luciana44

Oct 08, 2009 | The Learning Company Achieve! Math &...

6x- 3 = y; (0, -3)

Here 6x - 3 = y is the equation

The ordered pair is (0, -3 )

It means if you substitutes 0 for x and -3 for y the equation will be true

Let us substitute and see:-

'6x' (means 6 times x) means 6 times 0 which is equal to 0

So the equation 6x - 3 = y becomes

0- 3 = -3 is correct

The ordered pair means the values of x and y which make the equation correct

Hope this is clear enough

Good luck

luciana44

Here 6x - 3 = y is the equation

The ordered pair is (0, -3 )

It means if you substitutes 0 for x and -3 for y the equation will be true

Let us substitute and see:-

'6x' (means 6 times x) means 6 times 0 which is equal to 0

So the equation 6x - 3 = y becomes

0- 3 = -3 is correct

The ordered pair means the values of x and y which make the equation correct

Hope this is clear enough

Good luck

luciana44

Sep 27, 2009 | The Learning Company Achieve! Math &...

You are probably entering the equation wrong. Dont do this: 3600=x(2+2) You have to enter the equation 3600=x*(2+2)

May 28, 2008 | Texas Instruments TI-89 Calculator

Sep 25, 2017 | Brother Office Equipment & Supplies

64 people viewed this question

Usually answered in minutes!

×